2013
DOI: 10.1007/s10461-013-0600-3
|View full text |Cite
|
Sign up to set email alerts
|

Does Effective Depression Treatment Alone Reduce Secondary HIV Transmission Risk? Equivocal Findings from a Randomized Controlled Trial

Abstract: Depressed mood has been associated with HIV transmission risk behavior. To determine whether effective depression treatment could reduce the frequency of sexual risk behavior, we analyzed secondary outcome data from a 36-week, two-arm, parallel-design, randomized controlled trial, in which homeless and marginally housed, HIV-infected persons with comorbid depressive disorders were randomized to receive either: (a) directly observed treatment with the antidepressant medication fluoxetine, or (b) referral to a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Accordingly, results may not generalize to HIV-positive younger adults or those living in rural areas or metropolitan areas in other regions of the United States. Our null treatment findings do, however, converge with those of Tsai and colleagues [16] who enrolled a sample that is demographically and geographically distinct from participants in the current study. Second, as noted previously, this was not a sexual risk reduction trial, and these secondary data analyses were not powered to detect treatment effects on sexual behavior outcomes.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Accordingly, results may not generalize to HIV-positive younger adults or those living in rural areas or metropolitan areas in other regions of the United States. Our null treatment findings do, however, converge with those of Tsai and colleagues [16] who enrolled a sample that is demographically and geographically distinct from participants in the current study. Second, as noted previously, this was not a sexual risk reduction trial, and these secondary data analyses were not powered to detect treatment effects on sexual behavior outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with the current study, Tsai and colleagues [16] identified no differential reductions in sexual risk behavior by treatment condition in a randomized controlled trial of fluoxetine versus community mental health referral for HIV-positive homeless and marginally housed middle-aged adults in San Francisco, despite fluoxetine demonstrating superiority to community mental health referral in reducing depressive symptoms, with large treatment effects. Participants in this trial, however, also reported low rates of sexual risk behavior at baseline.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations